Разбой в открытом море - Зверев Сергей Иванович (Морской спецназ, 2012)
Экземпляры: аб. ЦБ (20200323) / Инвентарный номер: 9014 / Цена: / Сис.шифр: 84 (2Рос=Рус)6 / Авт.знак: З-43 / ГРНТИ: 17 / ББК: 84 (2Рос=Рус)6